Estado democrático de direito, direito penal e os serviços de telecomunicações - Ferreira, Danilo Augusto (2010)
Communicating through speech, distinguishes humans from other animals living among the world. Justified, therefore, the choice of the theme of this thesis, taking into consideration the fundamental right of free expression of thought or free expression. However, there is a growing trend of law, and more, the trend also an increasing trend in criminal law protect the legal interests which, in theory and in agreement with the guidelines established by the social model established with the advent of the promulgation of the Constitution Federative Republic of Brazil, from October 5, 1988, should not it be subject to safeguards. However, the objective is to present work to determine the meaning of democratic rule of law, its scope and its limitations, consolidating the constitution is an instrument of state activity adjacent to the forehead of fundamental rights and guarantees in them. The Penal Law constitute the field of law that a greater quantity and quality violates individual liberty, it will examine its mission and its approval of constitutional expertise, particularly with regard to inherent limitations and, apparently conflicting, to freedom of expression and thus the rights to inform, to inform and be informed